2012
DOI: 10.1371/journal.ppat.1002670
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent TLR3 Expression of the Intestinal Epithelium Contributes to Rotavirus Susceptibility

Abstract: Rotavirus is a major cause of diarrhea worldwide and exhibits a pronounced small intestinal epithelial cell (IEC) tropism. Both human infants and neonatal mice are highly susceptible, whereas adult individuals remain asymptomatic and shed only low numbers of viral particles. Here we investigated age-dependent mechanisms of the intestinal epithelial innate immune response to rotavirus infection in an oral mouse infection model. Expression of the innate immune receptor for viral dsRNA, Toll-like receptor (Tlr) 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
151
1
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(169 citation statements)
references
References 40 publications
9
151
1
8
Order By: Relevance
“…We could confirm the low transcriptional activity of TLR3 in whole organ intestinal samples of neonatal mice, which was not upregulated after pIC treatment either (Supplementary Figure S2 online). In contrast, it was previously shown that intestinal immune cells, such as macrophages, are not affected by this downregulation (28). Intestinal permeability (breastfed: n = 5, formula only, formula + pIC, and formula + LPS each n = 4).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…We could confirm the low transcriptional activity of TLR3 in whole organ intestinal samples of neonatal mice, which was not upregulated after pIC treatment either (Supplementary Figure S2 online). In contrast, it was previously shown that intestinal immune cells, such as macrophages, are not affected by this downregulation (28). Intestinal permeability (breastfed: n = 5, formula only, formula + pIC, and formula + LPS each n = 4).…”
Section: Discussionmentioning
confidence: 79%
“…injection of pIC (30 µg/g body weight (BW)) into adult mice induces mucosal injury in a TLR3-dependent manner and proposed a TLR3 dependency in the pathogenesis of viral gastrointestinal infections. In contrast, Pott et al (28) showed a reduced expression of TLR3 in the intestinal epithelium of neonatal mice as well as pediatric human small intestinal biopsies compared with adults. We could confirm the low transcriptional activity of TLR3 in whole organ intestinal samples of neonatal mice, which was not upregulated after pIC treatment either (Supplementary Figure S2 online).…”
Section: Discussionmentioning
confidence: 86%
“…Adult mice deficient in TLR--3 or the adaptor molecule had significantly higher viral shedding and decreased epithelial expression of proinflammatory and antiviral genes as compared to wild--type animals. In contrast, neonatal mice with the same deficiencies did not display these features, but increase of TLR--3 expression was observed over time and may be related to the age--dependent susceptibility to rotavirus infection 38 .…”
Section: Inflammatory Response To Rotavirus Infectionmentioning
confidence: 87%
“…Moreover, TLR--3 has been associated with rotavirus susceptibility, viral shedding and histological damage upregulation of epithelial TLR3 expression during infancy might contribute to the age--dependent susceptibility to rotavirus infection 38 . Adult mice deficient in TLR--3 or the adaptor molecule had significantly higher viral shedding and decreased epithelial expression of proinflammatory and antiviral genes as compared to wild--type animals.…”
Section: Inflammatory Response To Rotavirus Infectionmentioning
confidence: 99%
“…Rotaviruses are also important causes of diarrhea in animals and can manifest in 65 different disease severity depending on the age of the animals (Ciarlet et al, 2002; Neog et al, 66 2011;Pott et al, 2012;Riepenhoff et al, 1982). Although pigs of all ages are susceptible to 67 rotavirus infection, neonatal and even post-weaned piglets are frequently infected (Bohl et al, 68 1982;Lecce 1978).…”
mentioning
confidence: 99%